Sclerophyllous Forest Tree Growth Under the Influence of a Historic Megadrought in the Mediterranean Ecoregion of Chile - Venegas-Gonzalez, A.; Munoz, A. A.; Carpintero-Gibson, S.; Gonzalez-Reyes, A.; Schneider, I.; Gipolou-Zuniga, T.; Aguilera-Betti, I.; Roig, F. A. (My University, 2023)
The Mediterranean-type Ecosystems of Central Chile is one of the most threatened regions in South America by global change, particularly evidenced by the historical megadrought that has occurred in central Chile since 2010. The sclerophyllous forest stands out, whose history and relationship with drought conditions has been little studied. Cryptocarya alba and Beilschmiedia miersii (Lauraceae), two large endemic trees, represent an opportunity to analyze the incidence of intense droughts in the growth of sclerophyllous forests by analyzing their tree rings. Here, we considered > 400 trees from nineteen populations of C. alba and B. miersii growing across a latitudinal gradient (32 degrees -35 degrees S). To study the influence of local and large-scale climatic variability on tree growth, we first grouped the sites by species and explored the relationships between tree-growth patterns of C. alba and B. miersii with temperature, precipitation, and climate water deficit (CWD). Second, we performed Principal Component Analysis to detect common modes of variability and to explore relationships between growth patterns and their relationship to Palmer Drought Severity Index (PDSI), ENSO and SAM indices. We detected a breaking point as of 2002 at regional level, where a persistent and pronounced decrease in tree growth occurred, mainly influenced by the increase in CWD and the decrease in winter-spring rainfall. In addition, a positive (negative) relationship was showed between PC1 growth-PDSI and PC1 growth-ENSO (growth-SAM), that is, growth increases (decreases) in the same direction as PDSI and ENSO (SAM). Despite the fact that sclero phyllous populations are highly resistant to drought events, we suggest that the sclerophyllous populations studied here experienced a generalized growth decline, and possibly the natural dynamics of their forests have been altered, mainly due to the accumulating effects of the unprecedented drought since 2010.
Keywords: beilschmiedia miersii; chilean forests; cryptocarya alba; dendroecology; global change; increased drought condition; mediterranean forests; tree rings